Traditional Jump Rope as a Means of Deconstructing Digital Hegemony in Early Childhood: A Critical Ethnographic Study in Manado, Indonesia - Thofan Rame; Melius Lahagu; Jiffry Kawung (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
Digital hegemony increasingly governs how young children play in urban Indonesia, narrowing physical movement and direct social interaction in favour of screen-based activity. This study examined whether a traditional game, jump rope, can serve as a means of deconstructing that dominance among children aged four to six in Manado, North Sulawesi. A qualitative critical-ethnographic design was used. Data were gathered through participatory observation of jump-rope sessions, in-depth interviews with parents and educators, and visual documentation, with the researcher acting as the main instrument supported by a child-engagement observation guide and field notes. Analysis followed three deconstruction stages, identification of hierarchy, inversion, and reconstruction, and trustworthiness was established through source and time triangulation. Findings indicate that gadget use is normalised through tacit social consent and that traditional play has been marginalised. Reintroducing jump rope shifted children from passive screen use toward active collective play and was associated with greater patience in turn-taking, acceptance of losing, expressed empathy, and improved eye-hand-foot coordination and balance. Sustained change depended on parents and educators who deliberately limited gadget use, while the game transmitted local Mapalus values of cooperation and solidarity. The study concludes that jump rope operates as a culturally grounded means of deconstructing digital dominance without rejecting technology, offering a low-cost, context-sensitive route to supporting children's holistic motor, social, and cultural development.